Beyond Rides: Designing Internal Digital Systems for Dynamic Organization - Creating Guidelines for a Graphical Interface in Theme Park Organizations - Blomberg, Josefine; Vorberg, Amanda (My University, 2026)
The rapid digitalization of todays society, along with the emerging technologies it entails, places increasing demands on organizations and companies to adopt and implement digital systems. There are generally various systems being used simultaneously, and in order to remain effective and competitive, these need to have a high degree of user-friendliness in terms of being accessible, intuitive, and easy to use. This is of particular importance when it comes to organizations with high staff turnover, which is often the case in specifically service-based entertainment and leisure businesses. Among these are amusement park organizations, which typically rely heavily on seasonal employment, resulting in a constant flow and onboarding of new employees. Despite extensive research on usability in design and user experience (UX), there is a lack of studies regarding these aspects in relation to high employee turnover rates. This thesis project was carried out in collaboration with the amusement park Liseberg as a stakeholder, and the digital applications Gästis and Opening Hours as parts of their internal systems. The aim was to investigate what type of design approaches and practices best support usability in user interfaces (UIs) within organizations experiencing frequent employee turnover. The exploration was done by following the Double Diamond design process, with a total of three iterations. A user-centered approach was adopted, which involved semi-structured interviews and user tests conducted with employees at Liseberg, who regularly use any of the applications as part of their work role. The primary outcome of this study is the contribution to user-friendly UIs designed for use in high turnover organizational environments. The project resulted in the development of two high-fidelity prototypes in Figma, called Gästis 2.0 and Opening Hours 2.0, alongside a set of formulated design guidelines that can serve as a foundation for future investigation and improvement. The most important design guidelines identified are ensuring consistency across the interface, supporting efficient information scanning, providing clear and immediate system feedback, and following a structured and iterative design process. However, further research is recommended in order to validate feasibility and applicability of these guidelines beyond the specific context of this thesis.
Keywords: UI, UX, interaction design, digital systems, employee turnover, amuse ment park, prototyping, design guidelines, onboarding.